Anatomia e morfologia do sistema nervoso do diplópodo Gymnostreptus olivaceus (Spirostreptida, Spirostreptidae) e avaliação dos efeitos do inseticida deltametrina neste sistema - Francisco, Annelise [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Diplopods are ecologically important soil organisms that may also act as economically damaging species in urban and rural areas when their populations undergo outbreaks. They are, therefore, sometimes targetedfor agrochemicals action. Thus, some insecticides (e.g., deltamethrin) have been applied in order to control diplopods home invasions and crop attacks. Deltamethrin is characterized by its action on the nervous system; however, its effects on diplopods have yet to be analyzed. Additionally, there are few studies on the morphology and structure of the nervous system of diplopods. The present study aimed to elucidate the anatomy and morphology of the nervous system of the species Gymnostreptus olivaceus through direct observation during dissection under a stereomicroscope and by histological, histochemical, and cytochemical analyses. It was observed that the nervous system of the species consists of a brain and ventral nerve cord that are both wrapped by a perineurium, a neural lamella, and, more externally, by an external cell sheath that was first described in Diplopoda. Histological details were described for each of this species' nervous system structures. Furthermore, a commercial formulation of deltamethrin was applied to evaluate the effectiveness of the popular use of this insecticide to combat diplopods infestations. In order to observe neurotoxic effects caused by the insecticide, a synapsin labeling was used and assessed by confocal microscopy. Four concentrations of deltamethrin were applied topically to G. olivaceus individuals; the lowest concentration was based on the manufacturer's recommendations for controlling other arthropods, while the other concentrations correspond to one fifth of the LD50 previously established for the species, the LD50 itself, and twice the LD50. Death numbers were evaluated and synapsin levels were assessed in the brain at 12, 24 and 48 hours after insecticide treatment. The insecticide was...

Os diplópodos configuram-se como organismos do solo ecologicamente importantes, mas também como espécies economicamente ameaçadoras em áreas rurais e urbanas quando ocorrem explosões populacionais; assim tais organismos configuram-se ora como alvo ora como vítima da ação de agroquímicos. Nesse sentido, alguns inseticidas, tal como a deltametrina, têm sido aplicados com o intuito de controlar a invasão de diplópodos nas residências. Tal inseticida é genericamente caracterizado por ter ação no sistema nervoso, no entanto, os efeitos deste sobre diplópodos ainda não foram analisados. Adicionalmente, existem poucos estudos sobre a morfologia e estrutura do sistema nervoso de diplópodos. Sendo assim, o presente trabalho objetivou primeiramente elucidar a anatomia e morfologia do sistema nervoso da espécie Gymnostreptus olivaceus por meio da observação durante a dissecção em estereomicroscópio e de análise histológica, histoquímica e citoquímica. Observou-se que o sistema nervoso dessa espécie é composto por um cérebro e um cordão nervoso, envolvidos por perineuro, lamela neural e mais externamente por um envoltório celular externo que foi descrito pela primeira vez em Diplopoda. Foram descritos os detalhes histológicos observados em cada estrutura que compõe o sistema nervoso da espécie. Além disso, uma formulação comercial do inseticida deltametrina foi aplicada com o intuito de avaliar a efetividade da utilização popular de tal inseticida no combate a infestações de diplópodos. Para a observação de efeitos neurotóxicos causados pelo inseticida foi utilizada a marcação de sinapsina avaliada por microscopia confocal. Foram aplicadas topicamente em indivíduos da espécie G. olivaceus, quatro concentrações de deltametrina; a menor concentração baseou-se nas recomendações do fabricante para o combate de outros artrópodes, enquanto as demais concentrações corresponderam a um quinto da DL50...
Keywords: Millipedes; Milípede; Microscopia confocal; Histologia veterinária; Inseticidas; Sistema nervoso